2007
DOI: 10.1152/ajpgi.00226.2007
|View full text |Cite
|
Sign up to set email alerts
|

A neurokinin-1 receptor antagonist that reduces intra-abdominal adhesion formation decreases oxidative stress in the peritoneum

Abstract: Oxidative stress has been implicated in intra-abdominal adhesion formation. Substance P, a neurokinin-1 receptor (NK-1R) ligand, facilitates leukocyte recruitment and reactive oxygen species (ROS) generation. We have shown in a rat model of adhesion formation that intraperitoneal administration of a NK-1R antagonist at the time of abdominal operation reduces postoperative adhesion formation. Thus we determined the effects of NK-1R antagonist administration on peritoneal leukocyte recruitment and oxidative stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 50 publications
0
28
0
3
Order By: Relevance
“…47 Tissue injury results in bleeding and the resulting local hypoxia perpetuates endothelial permeability 48 with serosanguinous tissue exudation and leakage of lymphatic fluid, in addition to collection of blood, which occurs from transected vessels. Hypoxia resulting from injury acutely promotes O 2 À generation while the trauma itself disrupts stromal mast cells with release of vasoactive substances such as histamine and kinins, which enhance underlying fibroblasts migration and neutrophil recruitment to the wounded sites, 49 as well as decreased fibrinolytic activity. 50 The accumulation of red and white blood cells, macrophages, platelets, and tissue exudates forms a fibrinous mass, which, if persists, provides a fibrin matrix from which adhesion development occurs.…”
Section: Tissue Injury Hypoxia Oxidative Stress and Transcription mentioning
confidence: 99%
“…47 Tissue injury results in bleeding and the resulting local hypoxia perpetuates endothelial permeability 48 with serosanguinous tissue exudation and leakage of lymphatic fluid, in addition to collection of blood, which occurs from transected vessels. Hypoxia resulting from injury acutely promotes O 2 À generation while the trauma itself disrupts stromal mast cells with release of vasoactive substances such as histamine and kinins, which enhance underlying fibroblasts migration and neutrophil recruitment to the wounded sites, 49 as well as decreased fibrinolytic activity. 50 The accumulation of red and white blood cells, macrophages, platelets, and tissue exudates forms a fibrinous mass, which, if persists, provides a fibrin matrix from which adhesion development occurs.…”
Section: Tissue Injury Hypoxia Oxidative Stress and Transcription mentioning
confidence: 99%
“…ECP is a specific marker of eosinophils (Ursaciuc et al, 2010;Shah et al, 2012;Beigelman, 2014;Smith et al, 2015), which is mainly activated and released by eosinophils and causes neurotoxicity and cytotoxicity. In addition, ECP induces release of histamine by mast cells, causing airway hyperresponsiveness, resulting in bronchial asthma attack (Reed et al, 2007;Choi et al, 2010;Chua et al, 2010;Ursaciuc et al, 2010;Wei et al, 2010;Braga et al, 2011;Olive et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In the same study, administration of neurokinin-1 receptor antagonist was reported to significantly increase the antioxidant capacity of the peritoneal fluid, which supports the suggestion that oxidative stress plays a role in adhesion formation. It was concluded in the study that reducing postoperative oxidative stress may result in decreased postoperative adhesions [30]. In the light of these data, drugs reducing oxidative stress were suggested to limit adhesion formation in animal models [8,31].…”
Section: Discussionmentioning
confidence: 99%